Perinatal deficiency in dietary omega‐3 fatty acids potentiates sucrose reward and diet‐induced obesity in mice. Issue 64 (15th September 2017) - Auguste, Stéphanie; Sharma, Sandeep; Fisette, Alexandre; Fernandes, Maria F; Daneault, Caroline; Des Rosiers, Christine; Fulton, Stephanie
Abstract: Insufficient dietary intake of essential omega‐3 polyunsaturated fatty acids (N‐3), especially during critical stages of development, is well‐associated with negative neurological and metabolic consequences. The increased availability and intake of foods rich in saturated fat coincides with reduced N‐3 consumption, yet how N‐3 dietary deficiency during perinatal development modulates motivation for palatable food and interacts with a high‐fat diet to affect body weight and emotional states is not clear. Pregnant C57Bl6 mice and pups were subjected to diets either deficient or adequate (control) in N‐3 until postnatal day 21. Adult male N‐3 deficient or control offspring were tested in a progressive ratio operant task for sucrose motivated behavior or given prolonged access to a saturated high‐fat diet or chow followed by measures of energy balance and anxiety‐like behavior in the elevated‐plus maze and open field test. Brain fatty acid profiles were measured via gas chromatography mass spectrometry. Perinatal dietary N‐3 deficiency lowered brain N‐3 levels, augmented the rewarding effects of sucrose, heightened diet‐induced weight gain and fat mass accumulation and diminished spontaneous physical activity. Finally, perinatal N‐3 deficiency increased anxiety‐like behaviour independent of diet in the open field but not in the elevated‐plus maze test. Insufficient dietary N‐3 during critical periods of developmental can amplify the obesogenic effects of saturated fat intake, enhance motivated behaviour for palatable foods and may elicit negative emotional states that can perpetuate overeating and obesity.